The Road Not Traveled : Education Reform in the Middle East and North Africa - World Bank (Washington, DC : World Bank, 2012)
This report focuses on the economic rather than the social and cultural dimensions of education. Its approach in answering the questions raised is analytical and comparative in nature. Education outcomes in the region are compared with education outcomes in other developing countries. The development impact of investment in education is considered in the context of the large body of literature on the subject. The education reform strategies in Middle East and North Africa (MENA) are assessed on the basis of a new analytical framework. Labor market outcomes are evaluated on the basis of how well these markets function, given past reform efforts. The feature of the report is that it covers all levels of instruction, not just basic, secondary, or higher education. Although the primary focus of the report is education, it was important to pay special attention to domestic labor markets and migration. After all, this is where the returns to education are determined and its impact on development made.